Having an active role with the community in health counseling in Pardomuan Motung Village, Ajibata District, Toba Samosir Regency - Sadeli, Achmad; Simarmata, Pratomi; Ario, Rexy (Talenta Publisher, 2019)
Health education is a method used to convey health information. Counseling can be done directly through the face-to-face method or by using mass media as a means of delivering information. Communities in Pardomuan Motung Village still lack knowledge about healthy lifestyles so health counseling needs to be done especially about healthy lifestyles. The results of this community service showed that direct health education and through mass media were significantly associated with a healthy lifestyle Pardomuan Motung Village community. Health education is a dominant factor in general care